Pengelolaan Jimpitan Warga Melalui “Aplikasi Bank Jimpitan” Untuk Mendukung Program Pemberdayaan Masyarakat Di Kota Kediri - Izzah, Abidatul; Bakhtiar, Yohan (Universitas Nusantara PGRI Kediri, 2021)
Jimpitan is one of flagship programs in RT 06, RW 02, Ngronggo, Kediri. This program is an activity to collect daily savings money which is stored in a container and hung in front of the yard along with a board that will be taken and collected by Siskamling officers every night. Unfortunately, sometimes there are differences between the officer records with the board, so residents need to report and go to the RT staff to justify. Therefore, this paper describes how to improve the ease of managing jimpitan by building an interactive tool that can be used easily and quickly. The tool built is in the form of online applications that can be accessed anytime and anywhere and it is designed like